2016
DOI: 10.1182/blood.v128.22.2432.2432
|View full text |Cite
|
Sign up to set email alerts
|

Genotype/Phenotype Correlations in 103 Children from 87 Families with Hereditary Spherocytosis

Abstract: Hereditary spherocytosis (HS) is the most common congenital hemolytic anemia in Caucasians. Patients with HS show a high degree of phenotypic variability from asymptomatic to transfusion dependence. Much of this variability stems from HS not being a single uniform disorder but instead being a collection of disorders involving mutations in 5 different genes (ANK1, SPTB, SPTA1, SLC4A1, and EPB42 ) encoding for the 5 major cytoskeletal proteins in red blood cells (ankyrin, β and α spectrin, band 3, and protein 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Among the mutations in other HS genes, there was a broad variability in phenotypic presentation. 13,2325 So, until now, a clear genotype-phenotype correlation in HS has not been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Among the mutations in other HS genes, there was a broad variability in phenotypic presentation. 13,2325 So, until now, a clear genotype-phenotype correlation in HS has not been observed.…”
Section: Introductionmentioning
confidence: 99%
“…This erythrocyte membranopathy is a clinically, biochemically, and genetically heterogeneous disorder in which the presenting phenotype is anemia (which can range from compensated to severe), jaundice, reticulocytosis, splenomegaly, gallstones, several spherocytes in a peripheral blood smear, and increased erythrocyte osmotic fragility [3,4]. Previous studies have shown that five genes (ANK1, SPTB, SPTA1, SLC4A1, and EPB42) encoding red blood cell (RBC) membrane or skeletal proteins are mutated in hereditary spherocytosis [5,6]. A deficiency in or the dysfunction of these proteins results in a reduced surface area-to-volume ratio of spheroidal-shaped red cells due to membrane loss (mostly the intrinsic protein-containing lipid bilayer) and decreased membrane mechanical stability and deformability, which are responsible for the selective trapping of these cells in the spleen [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Two large sample studies in Canada demonstrated that pediatric patients with variants in SPTA1 presented with more severe anemia and a tendency to suffer from splenectomy, and patients with SLC4A1 defects showed a milder phenotype with a higher level of (HGB) and lower reticulocyte counts (RET). 29,36 In addition, Tole et al 29 observed the highest RET in patients with variants of ANK1. The Indian study confirmed lower levels of HGB and MCV and increased RBC distribution width (RDW) in patients with variants in SPTA1 compared to SPTB and SLC4A1.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…However, clinical studies concerning genotype–phenotype correlation remain controversial. Two large sample studies in Canada demonstrated that pediatric patients with variants in SPTA1 presented with more severe anemia and a tendency to suffer from splenectomy, and patients with SLC4A1 defects showed a milder phenotype with a higher level of hemoglobin (HGB) and lower reticulocyte counts (RET) 29,36 . In addition, Tole et al 29 observed the highest RET in patients with variants of ANK1 .…”
Section: Genotype–phenotype Correlationmentioning
confidence: 99%